Role of CenH3/CENP-A in the regulation of centromere function and chromosome segregation - Lamy, Márcia Sofia Ribeiro, 1987- (2011)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2010